Comparison of the gut microbiota and metabolites between Diannan small ear pigs and Diqing Tibetan pigs - Guan, Xuancheng; Zhu, Junhong; Yi, Lanlan; Sun, Haichao; Yang, Minghua; Huang, Ying; Pan, Hongbin; Wei, Hongjiang; Zhao, Hongye; Zhao, Yanguang; Zhao, Sumei (Frontiers in Microbiology, 2023)
Host genetics and environment participate in the shaping of gut microbiota.Diannan small ear pigs and Diqing Tibetan pigs are excellent native pig breeds in China and live in different environments. However, the gut microbiota of Diannan small ear pigs and Diqing Tibetan pigs were still rarely understood. Therefore, this study aimed to analyze the composition characteristics of gut microbiota and metabolites in Diannan small ear pigs and Diqing Tibetan pigs. Fresh feces of 6 pigs were randomly collected from 20 4-month-old Diannan small ear pigs (DA group) and 20 4-month-old Diqing Tibetan pigs (TA group) for high-throughput 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC-MS) non-targeted metabolome analysis. The results revealed that Firmicutes and Bacteroidetes were the dominant phyla in the two groups. Chao1 and ACE indices differed substantially between DA and TA groups. Compared with the DA group, the relative abundance of Prevotellaceae, and Ruminococcus was significantly enriched in the TA group, while the relative abundance of Lachnospiraceae, Actinomyces, and Butyricicoccus was significantly reduced. Cholecalciferol, 5-dehydroepisterol, stigmasterol, adrenic acid, and docosahexaenoic acid were significantly enriched in DA group, which was involved in the steroid biosynthesis and biosynthesis of unsaturated fatty acids.3-phenylpropanoic acid, L-tyrosine, phedrine, rhizoctin B, and rhizoctin D were significantly enriched in TA group, which was involved in the phenylalanine metabolism and phosphonate and phosphinate metabolism. We found that significant differences in gut microbiota composition and metabolite between Diannan small ear pigs and Diqing Tibetan pigs, which provide a theoretical basis for exploring the relationship between gut microbiota and pig breeds.